Relationship among socioeconomic status, attitude toward science, school climate and students' science achievement: A cross-country comparison of TIMSS - Kaya, Metin (International Council of Associations for Science Education (ICASE), 2022)
Students' socioeconomic status (SES), school climate, and students' attitudes stand out as important factors that determine academic achievement. The current study investigated the relationship among SES, attitude toward science, school climate, and academic achievement comparatively in terms of countries. Trends in International Mathematics and Science Study 2019 data from Turkey, United Kingdom, and Singapore were used for comparison. The study adopted a correlation design for each comparison. The participants were eighth grade students from these three countries. The data were analyzed with Pearson product-moment correlation coefficient and hierarchical multiple regression. The Singapore sample had an auto-correlation problem, so it was not included in the regression analysis. SES explained 16.6% and attitude towards science explained 9.8% of the change in the academic achievement in the United Kingdom sample while these values were 21.9% and 14.4% for the Turkey sample, respectively. The sub-dimensions of the independent variable were also examined in the study. One the most important factors associated with students' academic achievement in Turkey is their SES. In this sense, the limitations of students in their access to home resources for learning are reflected negatively to their academic performance.
Keywords: Academic Achievement; Attitudes; School Climate; Socioeconomic Status; TIMSS Analysis